Roadblocks and resilience: A qualitative study of the impact of pediatric tuberculosis on Tanzanian households and solutions from caregivers. Issue 1 (2nd January 2023) - Petros de Guex, Kristen; Augustino, Domitila; Mejan, Paulo; Gadiye, Rehema; Massong, Cornel; Lukumay, Saning'o; Msoka, Perry; Sariko, Margaretha; Kimathi, Dafroza; Vinnard, Christopher; Xie, Yingda; Mmbaga, Blandina; et al.
ABSTRACT: Distinct from quantifying the economic sequelae of tuberculosis (TB) in adults, data are scarce regarding lived experiences of youth and their caregivers seeking and sustaining TB treatment in low income communities. Children ages 4–17 diagnosed with TB and their caregivers were recruited from rural and semi-urban northern Tanzania. Using a grounded theory approach, a qualitative interview guide was developed, informed by exploratory research. Twenty-four interviews were conducted in Kiswahili, audio-recorded and analyzed for emerging and consistent themes. Dominant themes found were socioemotional impacts of TB on households, including adverse effects on work productivity, and facilitators and obstacles to TB care, including general financial hardship and transportation challenges. The median percentage of household monthly income spent to attend a TB clinic visit was 34% (minimum: 1%, maximum: 220%). The most common solutions identified by caregivers to mitigate adverse impacts were transportation assistance and nutrition supplementation. To end TB, healthcare systems must acknowledge the total financial burden shouldered by low wealth families seeking pediatric TB care, provide consultations and medications locally, and increase access to TB-specific communal funds to mitigate burdens such as inadequate nutrition. Trial registration : planned sub-study of the registered prospective study, NCT05283967. Trial registration: ClinicalTrials.gov identifier: NCT05283967.